Enfermedad d Krabbe. Enfermedad degenerativa del SNC - Cazañas Aldama, David; Martínez, Ángel; Valdés Pérez, Trinidad; Guernica, Antonio (Revista Cubana de Pediatría, 2023)
Reporte de caso anátomo-clínico